CLINICAL AND LABORATORY FEATURES OF FOCAL MYOCARDITIS IN PREGNANT WOMEN - Sharipova, F.Kh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background. Disruption of the normal functioning of the cardiovascular system (CVD) in pregnant women presents a special problem, as cardiovascular diseases are the most common group of extragenital diseases in pregnant women and are one of the main causes of maternal and perinatal mortality. Purpose of the study: to assess the clinical and laboratory features of focal myocarditis in pregnant women. Materials and methods of research. The study is based on the examination data of 126 pregnant women who were observed during pregnancy and admitted to the Tashkent Perinatal Center. Among those who participated in the study, focal myocarditis was diagnosed in 74 pregnant women (main group), of which 22 (29.7%) had the established myocarditis during pregnancy, and 52 pregnant women (70.3%) had myocarditis before pregnancy. The control group consisted of 52 pregnant women without signs of myocarditis. Results. Heart rate in pregnant women with myocarditis is 8.9% higher than in pregnant women without cardiovascular system pathology. The study results showed that the average pulmonary pressure in pregnant women with myocarditis is statistically significantly higher by 38.6%, the dimensions of the left ventricle (both linear and volumetric) have a significant tendency to increase. A significant increase in the content of cardiovascular system markers (troponin I (cTnI), N-terminal B-type natriuretic peptide (NT-proBNP), and D-dimer) was established in the blood of pregnant women with focal myocarditis. Conclusion. The results of the study showed that the average pulmonary pressure in pregnant women with myocarditis is statistically significantly higher by 38.6%, the dimensions of the left ventricle (both linear and volumetric) have a reliable tendency to increase. In pregnant women with focal myocarditis, disorders of uteroplacental blood flow in the fetoplacental complex were characterized by changes in blood flow more often in the uterine arteries, which is associated with increased blood flow. A significant increase in the content of markers of the cardiovascular system (troponin I (cTnI), N-terminal natriuretic peptide of type B (NT-proBNP), and D-dimer in the blood of pregnant women was established.